Anticancer Activity of New Substituted Pyrimidines, Their Thioglycosides and Thiazolopyrimidine Derivatives - Mahmoud N. M. Yousif, Wael A. El-Sayed, Hebat-Allah S. Abbas, Hanem M. Awad, Nabil M. Yousif (Journal of Applied Pharmaceutical Science, 2017)
Novel functionalized pyrimidine, thioxopyrimidine, iminopyrimidine derivatives and their derived bicyclic thiazolopyrimidine compounds were synthesized. The substituted arylidine derivatives of the thiazolopyrimidine compounds were also prepared. Glycosylation of the thiopyrimidine derivative resulted in formation of the acetylated thioglycosides which were deacetylated to the free hydroxythioglycosides. The synthesized compounds were studied for their anticancer activity against hepatocellular carcinoma HepG-2, human prostate adenocarcinoma PC-3 and human colorectal carcinoma HCT-116 cell lines. Compounds 7c, 8a and 12a showed high activity against PC-3 cancer cells while compounds 11b and 12a revealed higher activity against HCT-116 cell line.
Keywords: Pyrimidines, Thiazolopyrimidines, Thioglycosides, Anticancer, HCT-116, PC-3.